The Influence of Electrospinning Parameters and Drug Loading on Polyhydroxyalkanoate (PHA) Nanofibers for Drug Delivery - Lee, Yan-Fen; Sridewi, Nanthini; Ramanathan, Surash; Sudesh, Kumar (International Journal of Biotechnology for Wellness Industries, 2017)
The impact of polymer concentration and drug loading on nanofiber morphology and diameter were investigated during electrospinning of polyhydroxyalkanoate nanofibrous films. Low molecular weight poly(3-hydroxybutyrate-co-4-hydroxybutyrate) [P(3HB-co-95 mol% 4HB)] required a 5-fold higher solution concentration than high molecular weight poly(3-hydroxybutyrate) [P(3HB)] to produce bead-free nanofibers. Loading the films with paclitaxel increased the initial polymer solution viscosity allowing larger diameter nanofibers to form. Furthermore, paclitaxel added at 1% (w/w) into 8 % (w/v) P(3HB-co-95 mol% 4HB) solution eliminated the formation of beads seen in solutions without the drug, at the same initial polymer solution concentration. In preliminary drug release studies, nanofiber mats consisting of large-diameter nanofibers with high drug loading released paclitaxel at a faster rate due to larger pore sizes. This was a consequence of the random packing of larger diameter nanofibers. However, the release pattern of nanofibers with low drug loading was much more consistent and controlled. Lastly, we have shown the potential applications of P(3HB-co-4HB) drug loaded nanofibers in the development of biocompatible drug eluting stents by directly coating a metal stent with a homogeneous layer of electrospun polymer.